Implementasi Pemanfaatan Media Pembelajaran untuk Meningkatkan Pemahaman Siswa pada Materi Fiqih Jenazah - Muhammad Irsyadi Abdillah; Dyah Ayu Fitriana; Arim Irsyadulloh Albin Jaya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to examine the implementation of learning media in the topic of fiqh of funeral rites at SMA 1 Ngawen and its impact on students’ understanding in Islamic Religious Education learning. This research uses a qualitative approach with a case study design conducted at SMA 1 Ngawen. Data were collected through observation, interviews with Islamic Religious Education teachers and students, and documentation of the learning process. The collected data were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the use of learning media such as videos demonstrating funeral management practices, teaching aids, and visual presentations can help students understand the material on the fiqh of funeral rites more clearly and practically. These media make the learning process more engaging, interactive, and easier for students to understand. In addition, the implementation of learning media also increases student participation in learning activities, especially during simulation practices of funeral management. Therefore, the appropriate use of learning media in teaching the fiqh of funeral rites can improve learning effectiveness and help students understand the proper procedures for managing a deceased person according to Islamic teachings. The implication of this study indicates that the use of learning media can enhance the effectiveness of learning the fiqh of funeral rites and help students understand the material more easily.